Students' Efforts in Improving English Vocabulary, A Qualitative Study at Al Ulum Junior High School - Resty Wahyuni; Khairun Nissa (English Teaching and Linguistics Journal (ETLiJ), 2026)
Vocabulary is the main foundation in learning English, because without adequate vocabulary mastery, students will find it difficult to understand and convey messages effectively. This study aims to describe in depth the various efforts made by Al-Ulum Junior High School students in improving their vocabulary mastery. Using a descriptive qualitative approach, data was obtained through semi-structured interviews and classroom observations of 30 purposively selected 8th grade students. The results revealed that students utilize a variety of learning strategies, ranging from recording new vocabulary in a special book, using digital-based learning applications such as Duolingo and YouTube, to repeating vocabulary independently outside of class hours. These strategies reflect the application of cognitive and memory strategies, and display a tendency towards self-directed learning. However, there are still some barriers, such as low self-confidence and limited practice of vocabulary use in real-life situations. The results of this study show that the presence of a supportive teacher and a positive learning environment are instrumental in increasing students' participation and confidence in using vocabulary when communicating daily. The findings are expected to be valuable input in developing teaching approaches that are more relevant, flexible, and in line with the needs and characteristics of learners in the current era.